Le Corbusier's plan for Buenos Aires. Useful explanations on the birth of the cities - Rigotti, Ana Maria (2016)
Intuited during Le Corbusier’s trip to Sudamerica in 1929 and developed in 1937, the plan for Buenos Aires contradicts general assumptions about his early urban theories. It is not a generic proposal that breaks with the inertia of geographical, histori- cal and formal precedents. On the contrary, it follows Marcel Poëte theory of the cities as organic souls whose destiny is registered in their birth. The Plan is founded on an interpretation of the geographic settings and proposes a metamorphosis of the city on their own footprints, such as they were sketched on a map of 1713. This radical change in Le Corbusier’s formal and theoretical presumptions is due to the intuition of buildings with engineering scale in contrast with the magnitude of the American landscape. Also to the material provided by a previous urban project for Buenos Aires by the Comisión de Estética Edilicia (1925) with a clear agenda for the urban future and a historical interpretation of its historical development filled with old maps and photographs: this publication acted as a hidden dossier and inspired Le Corbusier’s proposal.